2018
DOI: 10.1029/2017pa003290
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Abyssal NW Atlantic Water Masses Since the Last Glacial Maximum

Abstract: The notion of a shallow northern sourced intermediate water mass is a well evidenced feature of the Atlantic circulation scheme of the Last Glacial Maximum (LGM). However, recent observations from stable carbon isotopes (δ 13 C) at the Corner Rise in the deep northwest Atlantic suggested a significant contribution of a Northern Component Water mass to the abyssal northwest Atlantic basin that has not been described before. Here we test the hypothesis of this northern sourced water mass underlying the southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 82 publications
(212 reference statements)
1
41
0
1
Order By: Relevance
“…We present new 231 Pa/ 230 Th data (supported by εNd and δ 13 C) from the Bermuda Rise complementing the existing records of the last glacial cycle in high resolution for the Holocene. While εNd and δ 13 C data document the continuous presence of NADW in the deep NW Atlantic (with εNd showing an unradiogenic excursion due to variable input from the Labrador Sea (Howe, Piotrowski, & Rennie, 2016;Pöppelmeier et al, 2018;Pöppelmeier et al, 2019) supporting information S4 for model description). The red curve (including an uncertainty range of 20% accounting for the maximum error on the sedimentation rate) delineates the resulting sediment signal blurred by bioturbation As an example the scenarios of a hypothetical Atlantic Meridional Overturning Circulation reduction by 50% for 150 years is shown, which is expected to be still distinguishable from the observations.…”
Section: Resultsmentioning
confidence: 98%
“…We present new 231 Pa/ 230 Th data (supported by εNd and δ 13 C) from the Bermuda Rise complementing the existing records of the last glacial cycle in high resolution for the Holocene. While εNd and δ 13 C data document the continuous presence of NADW in the deep NW Atlantic (with εNd showing an unradiogenic excursion due to variable input from the Labrador Sea (Howe, Piotrowski, & Rennie, 2016;Pöppelmeier et al, 2018;Pöppelmeier et al, 2019) supporting information S4 for model description). The red curve (including an uncertainty range of 20% accounting for the maximum error on the sedimentation rate) delineates the resulting sediment signal blurred by bioturbation As an example the scenarios of a hypothetical Atlantic Meridional Overturning Circulation reduction by 50% for 150 years is shown, which is expected to be still distinguishable from the observations.…”
Section: Resultsmentioning
confidence: 98%
“…Increases in 231 Pa/ 230 Th from LGM to HS1 are less pronounced for the water depth interval from 3,500 to 4,200 m (Sites 1060, 1061, and 12JPC; Figures and ) featuring the highest LGM values of the northwestern Atlantic depth transect and thus calling for a weaker change in circulation strength between LGM and HS1. In contrast, the deepest Site 1062 features a more pronounced increase in 231 Pa/ 230 Th from the LGM to HS1, potentially due to an abyssal component of northern‐sourced glacial water mass during the LGM (Howe et al, ; Keigwin & Swift, ; Pöppelmeier et al, ). Accordingly, increases in 231 Pa/ 230 Th from the LGM to HS1 below 4,200 m indicate a weakening of glacial abyssal NSW water mass admixture.…”
Section: Discussionmentioning
confidence: 99%
“…Different reconstructions showed that during the Last Glacial Maximum (LGM) as well as during short northern hemispheric cold spells such as Heinrich Stadials 1 and 2 (HS1 and HS2) and the deglacial Younger Dryas (YD), the balance of these water masses shifted toward a predominance of SSW filling most of the deep western Atlantic reaching north as far as 50-60°N (Curry & Oppo, 2005;Gutjahr & Lippold, 2011;Marchitto & Broecker, 2006;Roberts et al, 2010). However, recent studies suggested the presence of a deep northern-sourced water mass in the northwestern Atlantic also during the LGM as derived from stable carbon isotopes (Keigwin & Swift, 2017) and εNd data (Howe et al, 2016;Pöppelmeier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the accuracy of ε Nd as a paleo water-mass proxy often depends on the knowledge of past end-member characteristics (Fig. 2b; Howe et al 2016a;Pöppelmeier et al 2018), the impact of non-conservative processes (blaser et al 2019), and the fidelity of the archive and extraction method used (blaser et al 2016;Du et al 2016).…”
Section: Improving Nd Isotope-based Reconstructions Of Water Massesmentioning
confidence: 99%
“…At the same time a better understanding of present-day Nd cycling through measurements along ocean sections and dedicated process studies at key locations, currently performed as part of the international GEOTrACES program (geotraces.org), will increase the reliability of interpretations based on Nd isotopes. Lippold et al 2016;Pöppelmeier et al 2018). Higher glacial ε Nd in the Atlantic is generally interpreted to indicate the presence of more Pacific-sourced water, but uncertainties in past end-member ε Nd and Nd concentrations complicate such interpretations.…”
Section: Improving Nd Isotope-based Reconstructions Of Water Massesmentioning
confidence: 99%